DINAMIKA PERKEMBANGAN PESANTREN MODERN TAFIZHIL QURAN YAYASAN ISLAMIC CENTRE SUMATERA UTARA 1982-2017 - Fatima Rahma Rangkuti, Siti Zubaidah, Salminawati (Pascasarjana UIN Sumatera Utara, 2018)
Abstract: This research aims to analyze: 1) the dynamics of the development of educator in Modernboarding school Tahfizhil Quran Islamic Center of North Sumatra Foundation, 2) the dynamics of thedevelopment of students in Modern boarding school Tahfizhil Quran Islamic Center of North SumatraFoundation, 3) the dynamics of the development of curriculum in Modern boarding school Tahfizhil QuranIslamic Center of North Sumatra Foundation, 4) the dynamics of the development of program in Modernboarding school Tahfizhil Quran Islamic Center of North Sumatra Foundation. This study uses qualitativemethods that have a history shaped. The results showed that: 1) the development of educators in Modernboarding school Tahfizhil Quran Islamic Center of North Sumatra Foundation 1982-2017 shows theexistence of dynamics. 2) learners in Modern boarding school Tahfizhil Quran in 1983 till 1986 totaled only14 persons, i.e. students program Cadre of Scholars, that is because the Cadre of Scholars programregistration opened to new students only once in three years. 3) there are four curriculums that used in thisboarding school i.e. curriculum Cadre of Scholars, curriculum of Tahfizh, curriculum of national andcurriculum of religious schools. 4) tahfizh program was opened in the boarding school in 1989 which wasthe first tahfizh institutions in the city of Medan.Penelitian ini bertujuan untuk menganalisa: 1) dinamika perkembangan pendidik di Pesantren ModernTahfizhil Quran Yayasan Islamic Centre Sumatera Utara, 2) dinamika perkembangan peserta didik diPesantren Modern Tahfizhil Quran Yayasan Islamic Centre Sumatera Utara, 3) dinamika perkembangankurikulum di Pesantren Modern Tahfizhil Quran, 4) dinamika perkembangan program tahfizh di PesantrenModern Tahfizhil Quran Yayasan Islamic Centre Sumatera Utara. Penelitian ini menggunakan metodesejarah kualitatif. Hasil penelitian menunjukkan bahwa: 1) perkembangan pendidik di Pesantren ModernYayasan Islamic Centre Sumatera Utara 1982-2017 menunjukkan adanya dinamika perkembangan. 2)Peserta didik di Pesantren Modern Tahfizhil Quran pada tahun 1983 sampai 1986 hanya berjumlah 14orang, yaitu santri program Kader Ulama, hal tersebut dikarenakan program Kader Ulama hanya membukapendaftaran murid baru sekali dalam tiga tahun. 3) Adapun kurikulum yang digunakan dalam Pesantrenini ada empat kurikulum yaitu kurikulum Kader Ulama, kurikulum Tahfizh, kurikulum Nasional dankurikulum Pesantren. 4) Program tahfizh dibuka di Pesantren Modern Tahfizhil Quran Yayasan IslamicCentre Sumatera Utara pada tahun 1989 yang merupakan lembaga tahfizh pertama di kota Medan.